2020
DOI: 10.1007/s00107-020-01608-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drying mode and feed per tooth rate on the fine dust creation in pine and beech sawing on a mini sash gang saw

Abstract: The experimental results of the study focused on the effect of drying processes of modified air drying and warm air-steam mixture drying of pine and beech wood on the size of sawdust particles created in cutting using PRW-15M sash gang saw, are presented in the paper. Particle size analysis of dry sawdust was performed using two methods—sieving method and laser diffraction analysis. The results showed that the drying process did not affect the general particle size distribution of the sawdust, but the content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Dust particle size analyses of beech wood studied by Rogoziński et al 2021 [ 26 ] showed that sawing beech wood dried with a mixture of warm air and steam at 105 °C results in an increase in the content of fine dust particles compared to air-dried wood, especially at low feed rate. Admittedly, this is not thermally treated but dried wood; however, the cited previous study points out a similar relationship to the results described in this work regarding wood species and feed speed [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dust particle size analyses of beech wood studied by Rogoziński et al 2021 [ 26 ] showed that sawing beech wood dried with a mixture of warm air and steam at 105 °C results in an increase in the content of fine dust particles compared to air-dried wood, especially at low feed rate. Admittedly, this is not thermally treated but dried wood; however, the cited previous study points out a similar relationship to the results described in this work regarding wood species and feed speed [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wood dust consists of small wood chips. The wood chips’ size depends mainly on the machining process, including the state of the tool cutting edges and the cutting process’s technical conditions and technological parameters [ 24 , 25 , 26 ]. The finest particles’ content also depends on the processed wood material [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The laser diffraction method overestimates the results of the particle size measurement of wood dust due to the non-spherical shape of particles. Long and thin particles can be recognized as spheres with a diameter equal to the particle length [61,71]. Therefore, in order to avoid this error, many complementary measuring methods should be used.…”
Section: Resultsmentioning
confidence: 99%
“…Color changes were more noticeable in sapwood than in red heartwood, and measurements corroborated this observation In [12], where the combination of hot-air drying and high-temperature drying of birch timber was used, the color change of wood during the high-temperature drying of birch timber could be effectively reduced using hot-air drying during the early phase of the drying process. Drying conditions and methods can affect the intensity of color change [13], but so can conditions during the cutting process, such as cutting forces [14,15] sawdust granularity [16,17], and physical properties [18][19][20].…”
Section: Introductionmentioning
confidence: 99%